Toward a smart tourism system for luwuk banggai: integrating ai assistant and interactive WebGis - Yahya, Ahmad; Ishak, Ishak; Yusr, Yusri (Institute of Computer Science (IOCS), 2025)
The tourism potential of Luwuk Banggai is constrained by the lack of comprehensive and interactive information. Limited data on destinations, routes, and personalized guidance reduces the overall tourist experience. AI and WebGIS technologies offer innovative solutions for building a smarter tourism ecosystem. This study designed and implemented a smart tourism system in Luwuk Banggai by integrating an interactive AI assistant and WebGIS. The objective is to enhance the tourist experience through accurate information, personalized recommendations, intuitive visualizations, and to support tourism managers in decision-making. A system development approach was employed, beginning with needs analysis and literature review. The design involved a modular architecture an AI module for natural language interaction and a WebGIS module for spatial visualization. The implementation utilized modern web technologies with a responsive user interface and a structured database. System testing was conducted using black box testing to assess functionality and reliability. The developed smart tourism system successfully integrated an AI assistant capable of answering questions and providing recommendations, alongside an interactive WebGIS that displays locations and routes. Testing results indicated that the system operated according to specifications, improving both information access and interactivity. The integration of the AI assistant and WebGIS within the Luwuk Banggai smart tourism system effectively enhances the tourist experience and the efficiency of tourism information management. This system contributes to sustainable tourism and opens opportunities for future service personalization and spatial data analytics